(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article analyzes the concepts of self-education and moral maturity in the work of Sayyid Burhoniddin Muhaqqiq Tirmizi "Ma’arif" from a scientific and pedagogical point of view. The study emphasizes the role of moral and spiritual values such as devotion, patience, humility, honesty and the harmony of science in the formation of professional and personal development skills in students. The article also considers didactic features, pedagogical methods and the possibility of their application in the process of modern education. The results show that the work "Enlightenment" is valued not only as a historical and mystical heritage, but also as an effective didactic source in strengthening moral and spiritual education in the education system today.